Performance Evaluation of Common Bean (Phaseolus vulgaris L.) Genotypes for Yield and Related Traits at Areka, Southern Ethiopia - Simon Yohannes; Gobeze Loha; Mesfin Kebede Gessese (Advances in Agriculture)
Common bean is a source of dietary protein and the second most important legume crop in Africa next to faba bean. In Ethiopia common bean is the most important legume as the source of protein and export commodity. Hence, development of commercial varieties is one of the major tasks to meet increasing demand of the stake holders. To this effect, understanding the genetic variability, heritability and association between grain yield and other agronomic traits is necessary for effective plant breeding program. In this context, a field experiment was conducted during 2016/2017 cropping season at Areka Agricultural Research Center in southern Ethiopia with the objective of evaluating common bean genotypes for yield and related traits and also estimate the variability present among the genotypes. Treatments consisted of thirty three common bean genotypes were laid out in a randomized complete block design (RCBD) with three replications. Common bean genotypes exhibited considerable variations for agronomic traits and grain yield. Majority of the traits; plant height, number of nodes, internode length, leaf area, LAI, biological yield, pods per plant, HI and HSW had higher PCV. Genotypic coefficient of variance (GCV) varied from 1.88% to 37.72% with the highest GCV recorded for HSW. Heritability in broad sense (H2) ranged from 0.52% to 95.33% with the highest value observed for HSW. The present study revealed significant variation among genotypes for traits considered except few insignificant traits. In addition, almost all the genotypes were well adapted to the study area and hence, the high yielding genotypes could be directly used as seed sources for production of common bean and some of the genotypes with best diseases resistance reaction, and with high heritability can possibly be used in common bean improvement program.